A Solution‐Processed Small‐Molecule Diketopyrrolopyrrole Dimer for Organic Solar Cells. Issue 9 (26th June 2014) - Niu, Zhixiao; Wang, Xue; Huang, Jianhua; Tang, Ailing; Sun, Yuxi; Zhan, Chuanlang
Abstract An easily‐accessible, solution‐processed diketopyrrolopyrrole (DPP) dimer, namely BDT(TDPP)2, with benzodithiophene (BDT)‐thiophene (T) as the conjugated bridge unit was synthesized. The UV/vis absorption spectrum of the DPP dimer is broad and covers 350–740 nm, and the HOMO and LUMO energies are estimated to be −5.21 eV and −3.54 eV, respectively, by electrochemistry tests, which match well with the energy levels of [6, 6]‐phenyl‐C71‐butyric acid methyl ester (PC71BM). Solution‐processed, small‐molecule solar cells were prepared with BDT(TDPP)2 as the donor material and PC71BM as the acceptor material. With chloroform used as the processing solvent, the high boiling‐point solvent 1, 8‐diiodooctane (DIO) was used as the co‐solvent. Through screening the donor/acceptor ratios (1:1) and the DIO content (0.2 % (v/v)), the best device afforded a power conversion efficiency of 3.90 %, with a short‐circuit current density (Jsc) of 9.85 mA cm−2, an open‐circuit voltage (Voc) of 0.71 V, and an fill factor of 0.57.